Flexible Versus Rigid Laryngoscopy: A Prospective, Blinded Comparison of Image Quality - Boles, Roger W.; Gao, William Z.; Johns, Michael M.; Daniero, James J.; Grant, Nazaneen N.; Rubin, Adam D.; Bhatt, Neel K.; Hapner, Edie R.; O'Dell, Karla (Journal of voice, 2023)
To compare flexible distal-chip laryngoscopy (FDL) and rigid telescopic laryngoscopy (RTL) in image quality and diagnostic ability. Prospective cohort study; blinded comparison. Eighteen normal adult subjects were recruited to undergo both FDL and RTL and normalized videos were recorded. Three blinded laryngologists compared the videos for color fidelity, illumination, resolution, and vascularity, and indicated superiority with FDL, RTL, or no difference. Raters also reported if an abnormality was seen and in which video it was better visualized. Videos for two subjects were repeated to assess intra-rater reliability, making 20 video comparisons across 3 raters for a total of 60 ratings. Differences in responses were analyzed via Mann-Whitney U and Pearson Χ2. Inter-rater reliability was assessed via Fleiss’ kappa, and intra-rater reliability was assessed via percent agreement. RTL was rated superior in all categories of image quality (47 vs 5 vs 8, P < 0.01; 47 vs 7 vs 6, P < 0.01; 51 vs 5 vs 4, P<0.01; 44 vs 9 vs 7, P < 0.01, respectively). An abnormality was seen 33 times with both modalities and 6 times with RTL only. When seen with both modalities, visualization was superior in RTL compared with FDL (29 vs 4, P <0.01). There was significant superiority of RTL in all categories of image quality, with slight inter-rater agreement for color fidelity, resolution, and vascularity. RTL was also significantly better for visualization of abnormalities. These findings suggest superior image quality in RTL compared with FDL, but further research is required to determine if this difference is clinically significant.